The Untranslated Regions of Classic Swine Fever Virus RNA Trigger Apoptosis - Hsu, Wei-Li; Chen, Chung-Lun; Huang, Shi-Wei; Wu, Chia-Chen; Chen, I-Hsuan; Nadar, Muthukumar; Su, Yin-Peng; Tsai, Ching-Hsiu (PloS one, 2014)
Classical swine fever virus (CSFV) causes a broad range of disease in pigs, from acute symptoms including high fever and hemorrhages, to chronic disease or unapparent infection, depending on the virus strain. CSFV belongs to the genus Pestivirus of the family Flaviviridae. It carries a single-stranded positive-sense RNA genome. An internal ribosomal entry site (IRES) in the 5' untranslated region (UTR) drives the translation of a single open reading frame encoding a 3898 amino acid long polypeptide chain. The open reading frame is followed by a 3' UTR comprising four highly structured stem-loops. In the present study, a synthetic RNA composed of the 5' and 3' UTRs of the CSFV genome devoid of any viral coding sequence and separated by a luciferase gene cassette (designated 5'UTR-Luc-3'UTR) triggered apoptotic cell death as early as 4 h post-transfection. The apoptosis was measured by DNA laddering analysis, TUNEL assay, annexin-V binding determined by flow cytometry, and by analysis of caspase activation. Contrasting with this, only trace DNA laddering was observed in cells transfected with the individual 5' or 3' UTR RNA; even when the 5' UTR and 3' UTR were co-transfected as separate RNA molecules, DNA laddering did not reach the level induced by the chimeric 5'UTR-Luc-3'UTR RNA. Interestingly, RNA composed of the 5'UTR and of stem-loop I of the 3'UTR triggered much stronger apoptosis than the 5' or 3'UTR alone. These results indicate that the 5' and 3' UTRs act together in cis induce apoptosis. We furthered obtained evidence that the UTR-mediated apoptosis required double-stranded RNA and involved translation shutoff possibly through activation of PKR.